The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1073/pnas.2005255117
|View full text |Cite
|
Sign up to set email alerts
|

Climate drives the geography of marine consumption by changing predator communities

Abstract: The global distribution of primary production and consumption by humans (fisheries) is well-documented, but we have no map linking the central ecological process of consumption within food webs to temperature and other ecological drivers. Using standardized assays that span 105° of latitude on four continents, we show that rates of bait consumption by generalist predators in shallow marine ecosystems are tightly linked to both temperature and the composition of consumer assemblages. Unexpectedly, rates of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 70 publications
3
17
0
Order By: Relevance
“…Our study provides a novel integration of large-scale experimental and observational approaches to explore interactions among communities of predators and prey. Our results expand the growing literature that shows stronger predation at lower latitudes in both marine and terrestrial systems (Schemske et al 2009, Roslin et al 2017, Reynolds et al 2018, Hargreaves et al 2019, Longo et al 2019, Freestone et al 2020, but contrast with studies that find consumption rates of standardized bait can peak at midlatitudes for some groups of marine predators (Musrri et al 2019, Roesti et al 2020, Whalen et al 2020. Subsets of predators may demonstrate different consumption patterns across latitude because of differences in abundance and composition of specific predator taxa or geographic variation in abiotic patterns along different coastlines.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study provides a novel integration of large-scale experimental and observational approaches to explore interactions among communities of predators and prey. Our results expand the growing literature that shows stronger predation at lower latitudes in both marine and terrestrial systems (Schemske et al 2009, Roslin et al 2017, Reynolds et al 2018, Hargreaves et al 2019, Longo et al 2019, Freestone et al 2020, but contrast with studies that find consumption rates of standardized bait can peak at midlatitudes for some groups of marine predators (Musrri et al 2019, Roesti et al 2020, Whalen et al 2020. Subsets of predators may demonstrate different consumption patterns across latitude because of differences in abundance and composition of specific predator taxa or geographic variation in abiotic patterns along different coastlines.…”
Section: Discussionsupporting
confidence: 79%
“…To quantify predation intensity, studies that span biogeographic scales often assess predation rates (Jeanne 1979, Bertness et al 1981, Heck and Wilson 1987, Roslin et al 2017, Hargreaves et al 2019, Longo et al 2019, Roesti et al 2020, Whalen et al 2020, which have clear value in estimating top-down forcing in a community. Multiple dimensions of the predator community, however, contribute to predation intensity beyond predation rates and can vary among regions.…”
Section: Introductionmentioning
confidence: 99%
“…We predicted: (i) that trait dispersion would increase with decreasing latitude as species interactions become more intense, and (ii) that abiotic filters would be strongest and result in clustering at higher latitudes and where biotic interactions are weak. While marine systems often show nonlinear variation in species diversity and interaction strength with latitude (peaking at mid-latitudes; [ 20 , 31 ]), our predictions are reasonable within the range of latitudes occupied by eelgrass (approx. 30–70° N).…”
Section: Introductionsupporting
confidence: 63%
“…On the other hand, selection for tolerance of extreme heat conditions could also cause trait clustering at low latitudes. Finally, patterns in community structure along latitudinal gradients could be dominated by idiosyncratic and historically contingent effects of predators, prey, competitors, and mutualists that vary among biogeographic provinces [ 17 20 ]. Local abiotic factors, habitat complexity, assemblage composition and adaptation to these local factors could further obscure broader geographical patterns of community assembly [ 17 , 21 ], stressing the importance of assessing patterns across multiple independent species pools.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding spatial and temporal variation in consumption is crucial for predicting how ecosystems will respond to global and local change, including warming climate and fishing impacts (Ling et al, 2009;Vergés et al, 2011). Although relative variation in primary production and producer biomass can be compared efficiently in both terrestrial and marine environments, the mobility, diet, and behavior of consumers (e.g., fishes) make their distribution and top-down impacts challenging to quantify, especially in marine habitats (Duffy et al, 2015;Fraser et al, 2020;Whalen et al, 2020). However, an increasing number of studies have demonstrated that top-down processes vary predictably across latitude within a handful of marine habitats (Freestone et al, 2011;Rodemann and Brandl, 2017;Musrri et al, 2019;Whalen et al, 2020;Lefcheck et al, 2021), which may give insight into fish presence and behaviors, and help with the interpretation of consumption processes (Ferreira et al, 2004;Navarrete et al, 2005).…”
Section: Introductionmentioning
confidence: 99%